2009
DOI: 10.1128/jcm.01332-09
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Real-Time PCR to Screening Critically Ill and Emergency-Care Surgical Patients for Methicillin-Resistant Staphylococcus aureus : a Quantitative Analytical Study

Abstract: The clinical utility of real-time PCR screening assays for methicillin (meticillin)-resistant Staphylococcus aureus (MRSA) colonization is constrained by the predictive values of their results: as MRSA prevalence falls, the assay's positive predictive value (PPV) drops, and a rising proportion of positive PCR assays will not be confirmed by culture. We provide a quantitative analysis of universal PCR screening of critical care and emergency surgical patients using the BD GeneOhm MRSA PCR system, involving 3,29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…In summary, in our setting, C−P+ discordant results were more frequently due to a lower specificity of the XP (false aspecific amplification) than to an hypothetic lower sensitivity of culture (detection by XP of noncultivable MRSA). This is in accordance with Herdman et al, who showed that, if a PCR-positive result was obtained without culture confirmation in a high-risk (surgical and critical care) patient population, the risk for these patients to develop MRSA colonization or infection in the following 3 months was not different from the risk encountered by those with a negative PCR result [21]. In the large majority of cases (67%), however, we could not find any explanation for these C−P+ discordances.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In summary, in our setting, C−P+ discordant results were more frequently due to a lower specificity of the XP (false aspecific amplification) than to an hypothetic lower sensitivity of culture (detection by XP of noncultivable MRSA). This is in accordance with Herdman et al, who showed that, if a PCR-positive result was obtained without culture confirmation in a high-risk (surgical and critical care) patient population, the risk for these patients to develop MRSA colonization or infection in the following 3 months was not different from the risk encountered by those with a negative PCR result [21]. In the large majority of cases (67%), however, we could not find any explanation for these C−P+ discordances.…”
Section: Discussionsupporting
confidence: 91%
“…We showed a sensitivity (60.7%) at the lower end and a specificity (97.3%) in the middle of the range of results previously published [6][7][8][9][10][20][21][22][23][24]. We analyzed the XP discrepant results and found that a specific MSSA genotype (MLST CC1) and a specific MRSA clone (A20-ST8-SCCmec IV var ) gave false-positive and false-negative results by XP, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…Among the samples confirmed by culture, all but one had a C T value of Ͻ34. Similar differences in C T values have been reported for the GeneXpert system (25.6 versus 31.4) (17) and the BD GeneOhm MRSA assay (30.6 versus 37.3) (18), indicating that the bacterial loads in culture-negative samples are lower than those in culture-positive samples. The clinical significance of these results remains to be determined.…”
supporting
confidence: 58%
“…One criticism of this meta-analysis is that the role of test sensitivity and speed of reporting on the success or failure of MRSA programmes was not investigated [25], i.e. a rapid test has little impact when the results are not made available to the clinician within 24 h. The use of rapid PCR assays may have less utility in settings with low MRSA endemicity [7,50]. Nevertheless, the high negative predictive value and rapid turn-around-time (TAT) of PCR screening and the ability to inform optimal bed use, particularly in the ICU setting, may outweigh the uncertainty of its low positive predictive value and higher cost [26].…”
Section: Performance Of Current Screening Testsmentioning
confidence: 99%
“…There may also be reimbursement incentives and decreased liability from a possible reduction in the number of MRSA infections acquired in healthcare centres. On the down side (particularly where the prevalence is low), universal screening may result in the unnecessary isolation of MRSA patients [2,7], an increase in psychological problems for those patients who are colonised and placed in isolation [8], and an increase both in laboratory and hospital costs.…”
Section: Active Screening Of Mrsa Carriers: Universal or Targeted?mentioning
confidence: 99%